1972
DOI: 10.1149/1.2404194
|View full text |Cite
|
Sign up to set email alerts
|

Jet Polishing of Semiconductors

Abstract: 4_-Clean, fiat, strain-free surfaces of Si, Ge, GaAs, and of the P(lll) faces of GaP were prepared by scanning jets of chemical polishing reagents across one side of the rotating slices. The Ga(lll) faces of GaP were electrochemically polished in the same apparatus. It was found possible to reduce the central areas of large diameter Si slices to thicknesses of tens of microns while retaining thick, mechanically strong rims with this technique by masking the edges of the slices. Whole slices of Si were also red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Electrolytic jets have also been employed in etching and finishing applications. A review of the reported literature in this area indicates that electrolytic jets are most frequently employed for electron microscopic sample preparation and for polishing semiconductor materials (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Electrolytes used are generally strong acid solutions.…”
mentioning
confidence: 99%
“…Electrolytic jets have also been employed in etching and finishing applications. A review of the reported literature in this area indicates that electrolytic jets are most frequently employed for electron microscopic sample preparation and for polishing semiconductor materials (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Electrolytes used are generally strong acid solutions.…”
mentioning
confidence: 99%
“…Further work has shown that an improved version of this equipment will not only polish slices of Si, GaAS, and GaP as well as Ge, but it can be used to shape silicon slices that have been masked. This work is reported in the third paper in this series (11).…”
mentioning
confidence: 76%
“…Therefore, the ( 1 1 1 ) B surface should be more chemically active than the (111) A surface. 24 The Ga faces are etched and the P faces are polished in aqua regia. Usually, the faces are distinguished by their chemical characteristics in halogen (for example Cl 2 ) saturated methanol 15 or in hot aqua regia.…”
Section: Discussionmentioning
confidence: 99%